1978
DOI: 10.1063/1.435659
|View full text |Cite
|
Sign up to set email alerts
|

An optical study of the temperature dependent scattering of the a exciton (polariton) of naphthalene

Abstract: High resolution (-0.1 em-I) one-photon absorption profiles of the a band of naphthalene at 31475 cm-J from pure strain-free mounted (PSF) crystals have been measured between -2 and 40 K. Low temperature linewidths (FWHM) as narrow as 0.4 cm-J have been observed. The a band profile exhibits an asymmetry which increases with the temperature. The high E side is close to Lorentzian at all temperatures (particularly for T;::' 8 K) and tails more steeply than the low E side. Arguments are presented for the asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This large difference indicates excitons with different scattering rates namely different degrees of coupling with the surrounding medium according to the nature of the excited dipole; this has not been investigated further in the present situation however comparable observations have already been made. For instance the absorption spectra of high quality Naphtalene crystals show differences of one order of magnitude in linewidths for the weakly and strongly absorbing Davydov component of the same excitonic transition [55]. This is also observed for the fundamental exciton of α-sexithiophene.…”
Section: Influence Of Birefringencementioning
confidence: 86%
“…This large difference indicates excitons with different scattering rates namely different degrees of coupling with the surrounding medium according to the nature of the excited dipole; this has not been investigated further in the present situation however comparable observations have already been made. For instance the absorption spectra of high quality Naphtalene crystals show differences of one order of magnitude in linewidths for the weakly and strongly absorbing Davydov component of the same excitonic transition [55]. This is also observed for the fundamental exciton of α-sexithiophene.…”
Section: Influence Of Birefringencementioning
confidence: 86%
“…The fits given in Fig. Since studies of the neutral excitonic 7rTr* dimer states of organic crystals such as anthracene (Port et al 1979) and naphthalene (Robinette et al 1978) had shown that the exciton-phonon coupling is weak but that the coupling of charge-transfer (CT) states of 1:1 7r-molecular donor-acceptor complexes is very strong (Haarer 1974), it was suggested that P* must possess a significant amount of CT character (Johnson et al 1990). Thus, P* (P_) couples to two types of phonons: the marker mode, which is a localized phonon (tosp, Ssp ) involving intermolecular motion of the monomers of the special pair; and low frequency protein phonons (w m, S).…”
Section: Rps Viridismentioning
confidence: 99%